2021
DOI: 10.1063/9.0000127
|View full text |Cite
|
Sign up to set email alerts
|

First-principles prediction of rare-earth free permanent magnet: FeNi with enhanced magnetic anisotropy and stability through interstitial boron

Abstract: Ab initio electronic structure calculations reveal that interstitial 2p elements (B, C, and N) have dramatic effects on the structural stability and intrinsic magnetic properties of L10-phase FeNi. Among the 3 possible interstitial impurities, only the B improves the L10-phase stability of FeNi and enhances its uniaxial magnetic anisotropy (0.7 MJ m−3) up to 2.6 MJ m−3. The underlying mechanism is elucidated in terms of single-particle energy spectra analyses along with atom- and orbital-resolved magnetocrysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Tian et al worked on the optimization of tetrataenite phase in terms of the order-disorder transformation 16 , the effect of pressure 17 and alloying 18 by non-magnetic (Al and Ti) or magnetic (Cr and Co) atoms. The effect of alloying was also investigated by other authors: Tuvshin et al 19 showed that the addition of B can improve both the phase stability and increase MAE up to 2.6 MJ/m 3 . Izardar et al 27 studied the interplay between chemical order and the magnetic properties and found that the reduction of chemical long-range order by 25% does not reduce the MAE significantly.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Tian et al worked on the optimization of tetrataenite phase in terms of the order-disorder transformation 16 , the effect of pressure 17 and alloying 18 by non-magnetic (Al and Ti) or magnetic (Cr and Co) atoms. The effect of alloying was also investigated by other authors: Tuvshin et al 19 showed that the addition of B can improve both the phase stability and increase MAE up to 2.6 MJ/m 3 . Izardar et al 27 studied the interplay between chemical order and the magnetic properties and found that the reduction of chemical long-range order by 25% does not reduce the MAE significantly.…”
Section: Introductionmentioning
confidence: 93%
“…However, such materials are extremely expensive and finding inexpensive analogs consisting of abundant elements with similar performance is one of the most urgent and challenging tasks in modern materials science 1,4,[8][9][10][11][12] . One of the most intensely discussed candidate is equiatomic FeNi [13][14][15][16][17][18][19] in the tetragonally ordered L1 0 structure (tetrataenite). It is characterized by MAE of ≈ 1.1−1.3 MJ/m 3 being comparable to Nd 2 Fe 14 B, but hampered by a much smaller reduction with increasing temperature 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The ferromagnetic composition range from 50 to 60% Mn with a temperature of about 650 K; moreover, the compound's theoretical energy product is 112 kJ/m 3 .For the applications of transformers, inductors, motors, generators, actuators, and sensors, Fe-based alloys are the extensively utilized magnetic materials. Here, Iron Nitride (Fe 16 N 2 ) [29] centric magnetic material is utilized. It yields environment-friendly raw materials having saturation Magnetic Flux density (2.9 T), as well as reasonably higher magnetic anisotropy constant (1.8 MJ/m 3 ); thus, it is regarded as the most promising RE-free magnet candidate.…”
Section: Different Permanent Magnetic Materialsmentioning
confidence: 99%
“…However, such materials are extremely expensive, and challenging task of finding cheaper analogs with the same properties is one of the most urgent in modern materials science 1,4, [8][9][10][11][12] . The mostly known candidate for the permanent magnet role is FeNi [13][14][15][16][17][18][19] of tetragonal structure (tetratenite), in which the magnetocrystalline anisotropy energy (MAE) of ≈ 1.1−1.3 MJ/m 3 is comparable to one of Nd-Fe-B (Nd 2 Fe 14 B), but with much smaller reduction in magnitude with increasing temperature 20 . Natural tetrataenite found in meteorites is a slightly Fe-rich (Fe: 50.47 ± 1.98 at.% and Ni: 49.6 ± 1.49 at.%) and has f ct structure with alternating layers of Fe and Ni along the c-axis 15,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Authors showed the dependence of the transition temperature on the doping and external conditions. Tuvshin et al 19 studied the effect of alloying also. They showed that addition of B, which is 2p element, can improve both the phase stability and increase MAE up to 2.6 MJ/m 3 .…”
Section: Introductionmentioning
confidence: 99%